An innovative strategy to recycle permeate in biologics continuous manufacturing process to improve material efficiency and sustainability. (2nd May 2022) - Madabhushi, Sri Ranganayaki; Huang, Chung‐Jr; Wang, Xiaowen; Bui, Ashley; Atieh, Tariq Bassam; Rayfield, William J.; Jayapal, Karthik P.; Lin, Henry
Abstract: Intensified perfusion processes are an integral part of continuous manufacturing for biopharmaceuticals which enable agile operations and significant reduction in cost of goods. However, they require large volumes of media to support robust cell growth and maintain high productivity, posing substantial challenges to operations, logistics, and process sustainability. This study explores a novel strategy for reprocessing and reusing permeate from perfusion cultures for mAb production. The concept was initially evaluated by recycling permeate, Protein A flow‐through (ProA FT) and CEX processed ProA FT in deep‐well plate mock perfusion and ambr® 250 perfusion formats. Further processing of ProA FT through a cation exchange depth filter before recycling reduced process impurities such as host cell proteins (HCPs) and DNA. However, a direct replacement of fresh media with spent media reduces nutrient depth which results in a concomitant reduction in productivity. In ambr® 250 bioreactors, recycling of ProA FT at 25%–50% replacement rates (defined as the fraction of recycled material in media) resulted in a 13%–30% reduction in cumulative productivity while maintaining product quality. To mitigate this, we used media concentrates which allowed independent modulation of media depth by replacing a portion of diluent WFI with recycled material. Results from deep‐well mock perfusion studies demonstrated that comparable or higher productivities relative to control can be achieved with this approach. Taken together, our study demonstrates the feasibility of recycling permeate in perfusion cultures. Process mass intensity (PMI) calculations reveal that this approach can meaningfully improve material efficiency by reducing water consumption, thereby enhancing overall bioprocess sustainability.